Investigating the use of text modifications in L2 reading - Miksalmina Miksalmina; Wawan Gunawan; Ruswan Dallyono (Passage, 2021)
Research on text modifications has been around since the 80s until the present day. These studies have come a long way from manual text modification methods to the use of computerized models in its present form. However, there seems to be no resolution to the question of whether modified texts can help language learning. This study went back to the basics, manually modifying a text to find out whether it can help non-native English readers’ English reading comprehension. A text taken from a semiotic textbook was modified using the text modification strategies outlined by Parker Chaudron (1987). The text was then given to an experiment group comprising of 7th semester students studying linguistics at Universitas Pendidikan Indonesia. Having read the text, these students were given a written test alongside a questionnaire. Their scores and their attitudes toward the modified text (from the written test the questionnaire, respectively) were taken to measure and compare with the scores and attitudes of a control group reading the original text. The results showed a difference between the scores of students in the control group and those in the experiment group, with the latter having more students who scored high. There are also more students in the experiment group with a positive attitude toward the text they read compared to those in the control group. However, the difference in scores proved to be statistically not significant, and also most students who viewed the modified text positively scored low on the written test. Keywords: Elaboration of text, simplification of text, text modifications